(untitled) (Research, Society and Development, 2021)
Previous studies point out the potential of bananas as nutraceutical food, especially due to the healthiness provided by resistant starch and antioxidant capacity. In addition, food industry is increasingly interested in developing new products. In this sense, this study aimed to establish the nutritional quality of whole purees of green and senescent ‘nanica’ banana. For that, products were created simulating the industrial scale, following the main unit operations. It was carried out an experiment in a 2 x 2 factorial design, corresponding to two products (green and senescent banana whole puree), under two processes (heat treatment 120 °C for five minutes followed by cooling at 10 ° C for five minutes and absence of heat treatment), using three repetitions for each product. Characterization was carried out by physical-chemical analyzes, frequency of bioactive compounds and antioxidant activity. Results were evaluated by comparative means test (p <0.05) and by multivariate plots analysis. In all tests physical-chemical characterization showed purees stability in terms of acidity (pH and titratable) and in relation to macronutrients, carbohydrates, proteins, lipids and fibers. The most promising results are related to bioactive compounds because, although there is a reduction of three classes after thermal processing of green banana purees samples, there was still considerable antioxidant action of these components.